2021
DOI: 10.1101/2021.05.10.443308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minimal functional alignment of ventromedial prefrontal cortex intracranial EEG signals during naturalistic viewing

Abstract: The ventromedial prefrontal cortex (vmPFC) has been thought to play an important role in processing endogenous information such as generating subjective affective meaning. Unlike sensory cortex, which processes exogenous information about the external world similarly across individuals, prior work has posited that vmPFC activity may be idiosyncratic to each individual, even when exposed to the same external stimulus. In this study, we recorded local field potentials (LFPs) from intracranial stereo electrodes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 116 publications
(235 reference statements)
0
4
0
Order By: Relevance
“…Although hyperalignment and SRM are most often applied to fMRI data [58], in principle these models are modality-independent. For example, one recent study found that applying SRM to intracranial recordings, taken taken as patients watched a movie, revealed a set of shared components that co-varied with the affective content of the movie [158]. The study replicated (using intracranial recordings) several key findings from related fMRI work [25].…”
Section: Across-participant Approachesmentioning
confidence: 62%
See 1 more Smart Citation
“…Although hyperalignment and SRM are most often applied to fMRI data [58], in principle these models are modality-independent. For example, one recent study found that applying SRM to intracranial recordings, taken taken as patients watched a movie, revealed a set of shared components that co-varied with the affective content of the movie [158]. The study replicated (using intracranial recordings) several key findings from related fMRI work [25].…”
Section: Across-participant Approachesmentioning
confidence: 62%
“…Each participant's data must first be mapped into the common representation space. This may be carried out using anatomical [3,60,149], functional [27,57,58,158], or other [130,137] alignment methods. Next, the inference procedure (i.e., the algorithm for estimating model parameters from the observed data) must learn both local parameters (i.e., parameters that are specific to each individual) and global parameters (i.e., parameters that are shared across individuals).…”
Section: Across-participant Approachesmentioning
confidence: 99%
“…Further, the vmPFC has been involved in self‐referenced evaluation such as self‐attributing personality traits or recalling autobiographical memories (Northoff et al, 2006 ; Svoboda et al, 2006 ). Not only during movie viewing but even in the absence of sensory stimulation (resting state), the vmPFC exhibits higher inter‐individual variations in neural responses as compared to other brain regions (see L. Chang et al, 2018 , L. J. Chang et al, 2021 , Hasson et al, 2010 , Hasson et al, 2004 , and Xie et al, 2021 , for naturalistic paradigms and Mueller et al, 2013 , for resting state).…”
Section: Introductionmentioning
confidence: 99%
“…Not only during movie viewing but even in the absence of sensory stimulation (resting state), the vmPFC exhibits higher inter-individual variations in neural responses as compared to other brain regions (see L. Chang et al, 2018, Hasson et al, 2010, Hasson et al, 2004, and Xie et al, 2021, for naturalistic paradigms and Mueller et al, 2013.…”
mentioning
confidence: 99%